2020
DOI: 10.1186/s43094-020-00042-0
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of lipophilic compounds in regards to bioavailability as self-emulsifying drug delivery system (SEDDS)

Abstract: Background: High lipophilicity and poor aqueous solubility are the endemic problems of new drug molecules. Sixty to seventy percent of these drugs are unable to solubilize completely in aqueous media, or have very low permeability. This hampers their oral absorption and further leads to their poor bioavailability. Various researches are in progress to overcome these limitations. Novel technologies like nano-carrier systems have become popular for improving the solubility of drugs. Main body: Lipid-based formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…Antitubercular drugs tend to be more lipophilic compared to other antimicrobials; 24 thus we were curious whether the trends in potency observed within the 3-thio-1,2,4-triazole series correlated to lipophilicity. We calculated the LogP values of all the analogs using the SwissADME online data 25, 26, 27 and plotted these values against IC 50 in Mtb . We observed that all compounds that were active against Mtb have cLogP values clustered between 3.1 and 6.5 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Antitubercular drugs tend to be more lipophilic compared to other antimicrobials; 24 thus we were curious whether the trends in potency observed within the 3-thio-1,2,4-triazole series correlated to lipophilicity. We calculated the LogP values of all the analogs using the SwissADME online data 25, 26, 27 and plotted these values against IC 50 in Mtb . We observed that all compounds that were active against Mtb have cLogP values clustered between 3.1 and 6.5 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Surfactant in the formulation plays a predominant role to increase the absorption of lipophilic drugs. Ethoxylated lipid surfactants such as Gelucire®, Labrasol® and Cre-mophor® had proved that they inhibit the P-GP modulated drug efflux [111][112][113]. The selection of surfactants is restricted since not very many are satisfactory for oral delivery.…”
Section: Surfactantsmentioning
confidence: 99%
“…Acceptable balance between lipid and water phases permits suitability of absorption, drug design and formulation. This required balance mainly depends upon chemical structure [16].…”
Section: Figure (2) Logp Of Reactants and Productsmentioning
confidence: 99%